THE STUDY OF THE ECOLOGY OF THE ALGAE OF SEWAGE AS BIOTECHNOLOGICAL DISCIPLINES - Mustafaeva Mamlakat Ismalovna (Web of Journals Publishing, 2025)
This article presents the natural composition and seasonal changes in algae treatment facilities of Bukhara region.
Keywords: Biological ponds, algoflora, waste water, dynamics, algae, bioproduct